Relasi Sikap Implisit Terhadap Motivasi Kerja Guru Pendidikan Khusus Menurut Perspektif Islam - Maharani, Salsabila; Karimulloh (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Teacher attitudes play a vital role in shaping their motivation and effectiveness, especially among educators working with students with special needs. However, limited success and challenging teaching conditions often lead to low work motivation and negative implicit attitudes. This study aims to analyze the relationship between implicit attitudes and work motivation among teachers of special needs students within an Islamic perspective. Using a qualitative approach, this research employs a literature study method by collecting and analyzing scholarly sources such as books, journal articles, and other academic works relevant to Islamic views on moral behavior, motivation, and education. The findings reveal that teachers’ implicit attitudes reflected through moral conduct and sincerity have a direct influence on their work motivation. Good moral character (akhlak) strengthens spiritual awareness and fosters intrinsic motivation to perform teaching duties sincerely as a form of worship to Allah. This study highlights the significance of integrating Islamic ethical values into teacher motivation frameworks, emphasizing that moral integrity and sincere intentions can enhance the performance and well-being of inclusive education teachers.